2021
DOI: 10.3390/cells10071584
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Obesity on Microglial Function: Immune, Metabolic and Endocrine Perspectives

Abstract: Increased life expectancy in combination with modern life style and high prevalence of obesity are important risk factors for development of neurodegenerative diseases. Neuroinflammation is a feature of neurodegenerative diseases, and microglia, the innate immune cells of the brain, are central players in it. The present review discusses the effects of obesity, chronic peripheral inflammation and obesity-associated metabolic and endocrine perturbations, including insulin resistance, dyslipidemia and increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 456 publications
(717 reference statements)
1
43
0
Order By: Relevance
“…LPS treatment leads to increased plasma corticosterone levels (Alexaki, 2021; Kanczkowski et al, 2013c, 2013b). Numerous studies have shown that elevated glucocorticoid levels are primarily driven by activation of the HPA axis, and coincide with increased circulating ACTH levels (Alexaki, 2021; Kanczkowski et al, 2013c, 2013b). This is accompanied by increased expression of genes related to steroid biosynthesis, as previously reported (Chen et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LPS treatment leads to increased plasma corticosterone levels (Alexaki, 2021; Kanczkowski et al, 2013c, 2013b). Numerous studies have shown that elevated glucocorticoid levels are primarily driven by activation of the HPA axis, and coincide with increased circulating ACTH levels (Alexaki, 2021; Kanczkowski et al, 2013c, 2013b). This is accompanied by increased expression of genes related to steroid biosynthesis, as previously reported (Chen et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Adrenalectomized rodents show increased mortality after induction of systemic inflammation, while glucocorticoid administration increases survival (Bertini et al ., 1988; Butler et al ., 1989). Similarly to any other stress stimulus, systemic inflammation activates the HPA axis leading to increased glucocorticoid release, which is required to restrain inflammation (Alexaki, 2021; Kanczkowski et al, 2013c, 2013a, 2013b). Adrenocortical cells were also reported to directly respond to inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…on two consecutive days and 1 h after the second dose, they were treated i.p. with LPS for 16 h. We focused on the effects of ENT-A010 in the hippocampus, since the hippocampus is strongly affected by peripheral inflammation and prone to neurodegeneration [61][62][63], and asked whether ENT-A010 affected the phenotype of hippocampal microglia. Staining of brain sections (including the hippocampal formation) from mice treated with ENT-A010, LPS or ENT-A010 + LPS for the microglial marker ionized calcium-binding adaptor molecule 1 (IBA-1) demonstrated that LPS treatment induced thickening of the branches and enlargement of the cell body of microglia, standing in accordance with previous studies [64,65].…”
Section: Ent-a010 Preserves the Homeostatic Phenotype Of Microglia In...mentioning
confidence: 99%
“…While neuroinflammation disrupts insulin sensitivity and leptin resistance (63), obesity reciprocally impairs microglia function (64). Central and peripheral inflammation processes are in constant communication and create feedback signaling that predisposes opioid-exposed individuals to adverse neurological and peripheral effects, i.e., cognitive and cardiometabolic deficits (65,66).…”
Section: Neural and Systemic Inflammation Of Opioidsmentioning
confidence: 99%